A study on test-taking techniques for TOEIC reading comprehension test by students at vietnam maritime university. M.A. Thesis Linguistics - Nguyễn, Thị Thi (ĐHNN, 2017)
This study was conducted at Vietnam Maritime University with a view to exploring test-taking strategies relative to learners’ performance in TOEIC Reading Comprehension as well as identifying differences in reading strategies among high proficiency and low proficiency students at Vietnam Maritime University.